EXAMINING THE SOYBEAN COMPETITIVENESS IN CENTRAL JAVA: A POLICY ANALYSIS MATRIX APPROACH - Setiawan, Avi Budi; Antriyandarti, Ernoiz; Yusuf, Mochammad; Bowo, Prasetyo Ari; Wiyanti, Dian Tri (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Soybean is one of the leading food crops in Indonesia, but its dependence on imports is very high. The productivity of soybean yields in Indonesia is also far below that of other soybean-producing countries. This study aims to analyze the competitiveness of soybean farming in Central Java Province. Policy Analysis Matrix (PAM) is used to analyze the soybean competitiveness. The results showed that the from PAM model shows that the PCR value is 0.37, which means that soybean farming is competitive in the current market. Furthermore, the DRC value is 0.30, indicating that soybean commodities have a comparative advantage or are competitive in the market if they are perfectly competitive and there are no distortions. Soybeans have an NPCO value of 0.960, farmers are paid 96% of what they should be paid. It appears that soybean farmers are relatively disadvantaged based on the NPCO value. Furthermore, the NPCI value is 0.98. The research results indicate that the NPCI has a value less than one. This implies the existence of consumer input protection policies in the form of subsidies. Thus, to meet domestic demand for soybeans, producing for domestic is better than importing from other countries. The and competitiveness analysis results show that soybean farming is profitable and competitive. The existence of competitive and comparative advantages indicates that soybean farming is still feasible to be cultivated domestically, so efforts are needed to increase efficiency to reduce dependence on imports.